Ceftazidime pharmacokinetics in dogs after intravenous injection and delivered with the RxActuator Mini‐Infuser infusion pump - Papich, Mark G.; Madsen, Melanie; Messenger, Kristen; Enomoto, Hiroko (Journal of veterinary emergency and critical care (San Antonio, Tex. : 2000), 2022)
Objective To test the feasibility of an SC mini‐infusion pump to deliver ceftazidime in dogs and produce plasma concentrations sufficient to reach a therapeutic target for 48 hours. Setting University research laboratory. Animals Six healthy Beagle dogs. Interventions Ceftazidime was administered by 2 routes to 6 healthy Beagle dogs. The first route was an IV bolus injection into a cephalic vein at a dose of 25 mg/kg. Blood samples were collected for 8 hours following injection. The second route was a SC infusion for 48 hours using the RxActuator Mini‐Infuser wearable SC constant rate infusion pump. Blood samples were collected for 58 hours following application of the pump. All plasma samples were analyzed by high‐pressure liquid chromatography and subject to pharmacokinetic analysis. Main Results After the IV bolus injection, there was rapid distribution and elimination. The elimination half‐life was 0.95 hours, and the clearance was rapid at 0.176 ml/h/kg. After the 48‐hour SC infusion, the half‐life was slightly shorter, and the clearance was higher. The percent bioavailability from the SC infusion was approximately 72%. The SC infusion maintained plasma concentration near our target of 8 μg/ml for most of the dose interval but slightly lower after 24 hours. The concentrations below the target were attributed to slight drug loss, less than 100% bioavailability, and faster clearance from SC administration. Conclusions This study demonstrated the successful application of the RxActuator Mini‐Infuser wearable SC constant rate infusion pump for delivering an antimicrobial needed for serious, and sometimes resistant, infections in dogs.